Japanese version of The Cancer Genome Atlas, JCGA, established using fresh frozen tumors obtained from 5143 cancer patients. Issue 2 (22nd January 2020) - Nagashima, Takeshi; Yamaguchi, Ken; Urakami, Kenichi; Shimoda, Yuji; Ohnami, Sumiko; Ohshima, Keiichi; Tanabe, Tomoe; Naruoka, Akane; Kamada, Fukumi; Serizawa, Masakuni; Hatakeyama, Keiichi; Matsumura, Kenya; et al.
Abstract: This study aimed to establish the Japanese Cancer Genome Atlas (JCGA) using data from fresh frozen tumor tissues obtained from 5143 Japanese cancer patients, including those with colorectal cancer (31.6%), lung cancer (16.5%), gastric cancer (10.8%) and other cancers (41.1%). The results are part of a single‐center study called "High‐tech Omics‐based Patient Evaluation" or "Project HOPE" conducted at the Shizuoka Cancer Center, Japan. All DNA samples and most RNA samples were analyzed using whole‐exome sequencing, cancer gene panel sequencing, fusion gene panel sequencing and microarray gene expression profiling, and the results were annotated using an analysis pipeline termed "Shizuoka Multi‐omics Analysis Protocol" developed in‐house. Somatic driver alterations were identified in 72.2% of samples in 362 genes (average, 2.3 driver events per sample). Actionable information on drugs that is applicable in the current clinical setting was associated with 11.3% of samples. When including those drugs that are used for investigative purposes, actionable information was assigned to 55.0% of samples. Germline analysis revealed pathogenic mutations in hereditary cancer genes in 9.2% of samples, among which 12.2% were confirmed as pathogenic mutations by confirmatory test. Pathogenic mutations associated with non–cancerous hereditary diseases were detected in 0.4% of samples. Tumor mutation burden (TMB) analysis revealed 5.4% of samples as having the hypermutator phenotype (TMB ≥ 20). Clonal hematopoiesis was observed in 8.4% of samples. Thus, the JCGA dataset and the analytical procedures constitute a fundamental resource for genomic medicine for Japanese cancer patients. Abstract : The present study aims to establish the Japanese Cancer Genome Atlas (JCGA) by analyzing fresh frozen tumor tissues obtained from 5143 Japanese cancer patients. Somatic driver and druggable alterations were detected in 72.2% and 11.3% of samples, respectively, and germline pathogenic mutations in hereditary cancer genes were identified in 9.2% of samples. The JCGA dataset and analytical procedures constitute a fundamental resource for genomic medicine for Japanese cancer patients.